1992
DOI: 10.1002/jcp.1041500312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of estrogen receptor mRNA and the estrogen modulation of parathyroid hormone‐stimulated cyclic AMP accumulation in opossum kidney cells

Abstract: The opossum kidney (OK) cell was used as a model to test the hypothesis that estrogen directly affects proximal renal tubular epithelial cells. To demonstrate the expression of estrogen receptor in OK cells, we developed an approach using reverse transcription and the polymerase chain reaction. Analysis of the DNA amplified with nested primers revealed the predicted size fragment and restriction enzyme digestion products. To demonstrate the functional effects of estrogen, OK cells at confluence were preincubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…(54) In laying hens, 17␤-E 2 reduces PTH receptor binding affinity in calvaria and kidney. (55) However, estrogen substitution in postmenopausal women may result in either unchanged (19,49,54) or increased renal 1␣-hydroxylase activity, either due to increased serum PTH levels (30) or an increased renal responsiveness to PTH. (56) Furthermore, Ash et al have shown in a rat model that estrogens promote PTH-induced synthesis of calcitriol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(54) In laying hens, 17␤-E 2 reduces PTH receptor binding affinity in calvaria and kidney. (55) However, estrogen substitution in postmenopausal women may result in either unchanged (19,49,54) or increased renal 1␣-hydroxylase activity, either due to increased serum PTH levels (30) or an increased renal responsiveness to PTH. (56) Furthermore, Ash et al have shown in a rat model that estrogens promote PTH-induced synthesis of calcitriol.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10)(11) These effects can be direct and/ or indirect via regulation of and/or interaction with other factors influencing bone metabolism, e.g., parathyroid hormone (PTH) and insulin-like growth factor I. (12)(13)(14)(15)(16)(17) Menopause is associated with decreased calcium absorption, (18) which can be normalized by 17␤-E 2 supplementation. (19,20) A positive regulation of intestinal calcium absorption by estradiol has been suggested by Arjmandi et al (21) Therefore, modulation of intestinal calcium absorption could be a target for estradiol and selective estrogen receptor modulators in postmenopausal osteoporosis.…”
mentioning
confidence: 99%
“…In the kidney, however, the action of estrogen on adenylate cyclase is less well defined; Imanaka et al (1998) reported that estrogen administration to elderly women enhances cAMP excretion induced by PTH loading. In contrast, 17 -estradiol has been shown to inhibit the PTH-dependent cAMP release in opossum kidney cells (Stock et al 1992). In the renal distal tubule, we previously showed that either cAMP alone, or the combined cAMP and protein kinase C activation, increases rather than decreases Ca 2+ transport by the luminal membrane (Hilal et al 1997).…”
Section: What Messengers Are Involved In the Estrogen Actions?mentioning
confidence: 92%
“…Moreover, in vivo regulation of calciuria is complex. In addition to its effect on bone, estrogen has been shown to interfere with the PTH-dependent cAMP synthesis in opossum kidney cells (Stock et al 1992) and to stimulate both the vitamin D active metabolite 1,25(OH 2 )D 3 (Tanaka et al 1978, Cheema et al 1989, Castillo et al 1977 and calbindin 28K (Gill & Christakos 1995) expression. Not only does 1,25(OH 2 )D 3 increase Ca 2+ intestinal absorption but it also directly regulates PTH secretion by the gland (Chertow et al 1980, Russel et al 1986, Silver et al 1986, which is a site of receptors for this hormone (Brumbaugh et al 1975).…”
Section: Estrogen Decreases Tubular Reabsorption Of Ca 2+ In the Distmentioning
confidence: 99%
“…The localization of estrogen receptors in OK cells (Stock et al, 1992), along with the expression of OC transport function (McKinney et al, 1990;Yuan et al, 1991;Endo et al, 2000), makes this renal culture an appropriate model system for investigating estrogen regulation of OC transport. The data reported here demonstrate that the endogenous estrogen 17␤-E 2 and the synthetic pharmaceutical estrogen DES reduce TEA transport across the basolateral membrane of OK cells.…”
mentioning
confidence: 99%